Electron transfer between carotenoid and chlorophyll contributes to quenching in the LHCSR1 protein from Physcomitrella patens - Pinnola, Alberta; Staleva-Musto, Hristina; Capaldi, Stefano; Ballottari, Matteo; Bassi, Roberto; Polívka, Tomáš (Biochimica et biophysica acta, 2016)
Plants harvest photons for photosynthesis using light-harvesting complexes (LHCs)-an array of chlorophyll proteins that can reversibly switch from harvesting to energy-dissipation mode to prevent over-excitation and damage of the photosynthetic apparatus. In unicellular algae and lower plants this process requires the LHCSR proteins which senses over-acidification of the lumen trough protonatable residues exposed to the thylakoid lumen to activate quenching reactions. Further activation is provided by replacement of the violaxanthin ligand with its de-epoxidized product, zeaxanthin, also induced by excess light. We have produced the ppLHCSR1 protein from Physcomitrella patens by over-expression in tobacco and purified it in either its violaxanthin- or the zeaxanthin-binding form with the aim of analyzing their spectroscopic properties at either neutral or acidic pH. Using femtosecond spectroscopy, we demonstrated that the energy dissipation is achieved by two distinct quenching mechanism which are both activated by low pH. The first is present in both ppLHCSR1-Vio and ppLHCSR1-Zea and is characterized by 30-40ps time constant. The spectrum of the quenching product is reminiscent of a carotenoid radical cation, suggesting that the pH-induced quenching mechanism is likely electron transfer from the carotenoid to the excited Chl a. In addition, a second quenching channel populating the S1 state of carotenoid via energy transfer from Chl is found exclusively in the ppLHCSR1-Zea at pH5. These results provide proof of principle that more than one quenching mechanism may operate in the LHC superfamily and also help understanding the photoprotective role of LHCSR proteins and the evolution of LHC antennae.
Keywords: spektrální analýza; Light-Harvesting Protein Complexes; mechy; fotosyntéza; Protein Binding; transport elektronů; přenos energie; xanthofyly; Models, Biological; Energy Transfer; Nicotiana; geneticky modifikované rostliny; koncentrace vodíkových iontů; Zeaxanthins; biologické modely; Xanthophylls; Plants, Genetically Modified; Bryopsida; vazba proteinů; Kinetics; chlorofyl; tabák; Photosynthesis; kinetika; světlosběrné proteinové komplexy; Spectrum Analysis; Hydrogen-Ion Concentration; zeaxanthiny; Electron Transport; Chlorophyll